2020
DOI: 10.3329/ajmbr.v6i2.48043
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on food safety and security in low and middle income countries

Abstract: The occurrence of COVID-19 which causes severe acute respiratory infection has produced a large global outbreak with major public health concern. Since Chinese wet market (LBM) has been blamed to be linked with this global pandemic of COVID-19 as the noble virus has supposed to be transmitted from a wild species, however, this is not yet established the association of SARS-Cov-2 transmission via animal to human or food chain. Moreover, it has been recognized to spread human-to-human transmission by inhalation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 11 publications
0
20
0
Order By: Relevance
“…Reducing safety risks requires close cooperation with departments, investors, and local administration organizations. Commitment among management and decision makers on food safety issues, coordination and partnership among local governments, shareholders and nations, distribution of adequate capitals and accountability from all interested party are necessary to achieve food safety [5].…”
Section: Research Background and Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Reducing safety risks requires close cooperation with departments, investors, and local administration organizations. Commitment among management and decision makers on food safety issues, coordination and partnership among local governments, shareholders and nations, distribution of adequate capitals and accountability from all interested party are necessary to achieve food safety [5].…”
Section: Research Background and Literature Reviewmentioning
confidence: 99%
“…Given the vulnerability of the livestock value chains (including organic food products), immediate action is needed by the Chinese government to ensure the survival of the livestock sector during the COVID-19 pandemic and to restore the livelihoods of livestock and poultry breeders. Manufacturers should use BFTS to target various influencing factors, improve the public's willingness to use safe organic food products, and publicize the nutritional significance of animal-derived foods (meat, eggs, milk), to improve the overall health and immunity of the nation, and vigorously publicize that livestock and poultry are not related to the transmission of COVID-19 [5].…”
Section: Managerial Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, some researches have confirmed that similar to SARS-CoV-1 and other eight coronaviruses, the SARS-CoV-2 virus is expected to behave similarly at freezing temperatures, which means it could remain contagious under −20°C for up to 2 years ( Rizou et al, 2020 ). Therefore, perfect food safety measures are critical to controlling viral spread ( Uddin et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The SARS-CoV-2 novel coronavirus (herein called COVID-19 recognizing that this is the resultant disease) pandemic has had an incredibly heavy human toll (from loss of life (Woolf et al, 2020), to mental health crises (Tandon 2020), to loss of livelihoods (Dev 2020), to changes in food security (Uddin et al, 2020)) and rapid and dramatic effects on the world and how it functions. Major changes in human behaviour spanning travel patterns, consumerism, and energy use, among others, have influenced local and global biodiversity (e.g., Gillinghan et al, 2020;Rondeau et al, 2020;Zambrano-Monserrate et al, 2020).…”
Section: Introductionmentioning
confidence: 99%